2021
DOI: 10.1021/acs.jpcb.1c02150
|View full text |Cite
|
Sign up to set email alerts
|

Role of Conformational Change and Glucose Binding Sites in the Enhanced Glucose Tolerance of Agrobacterium tumefaciens 5A GH1 β-Glucosidase Mutants

Abstract: β-Glucosidases are often inhibited by their reaction product glucose and a barrier to the efficient lignocellulosic biomass hydrolysis to glucose. We had previously reported the mutants, C174V, and H229S, with a nearly 2-fold increased glucose tolerance over the wild type (WT), H0HC94, encoded in Agrobacterium tumefaciens 5A (apparent K i , Glc = 686 mM). We report our steady−state and time-resolved intrinsic fluorescence spectroscopy, circular dichroism, and isothermal titration calorimetry (ITC) studies to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…We previously reported that glucose might form multiple hydrogen bonds to H0HC94 through hydroxyl groups. 20,21 Our current simulations show that the average number of inter-hydrogen bonds between H0HC94 and substrates were 10 ± 3, 20 ± 4, 9 ± 3, and 15 ± 3 in S1, S2, S3, and S4, respectively (Supplementary Table S1; Figure 4a). Cellobiose formed comparatively more hydrogen bonds with both WT and mutant than pNPGlc.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…We previously reported that glucose might form multiple hydrogen bonds to H0HC94 through hydroxyl groups. 20,21 Our current simulations show that the average number of inter-hydrogen bonds between H0HC94 and substrates were 10 ± 3, 20 ± 4, 9 ± 3, and 15 ± 3 in S1, S2, S3, and S4, respectively (Supplementary Table S1; Figure 4a). Cellobiose formed comparatively more hydrogen bonds with both WT and mutant than pNPGlc.…”
Section: Resultsmentioning
confidence: 74%
“…A similar rmsd pattern was previously reported, signifying the overall structural stability of the enzyme under the studied timescales. 20, 21…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations